Blast effects on buildings - Cormie, David; Mays, Geoffrey; Smith, P. D., 1950 March 26- (ICE Publishing, 2019)
Blast Effects on Buildings showcases the latest practical guidance on designing buildings to optimise their resilience to blast loading. Focused specifically on the design of commercial buildings, it is an indispensable guide to help engineers reduce the risks posed to building occupants and businesses from terrorist attacks and other explosions. This new third edition has been fully updated and expanded to reflect the significant developments which have occurred in the field of blast engineering. Combining coverage of design standards, codes and materials with a detailed appreciation of the needs and demands of the designer, this book offers the engineer with a single and comprehensive source of reference for all the main elements of blast engineering design in modern practice.